Pengembangan Media Video Tutorial Dalam Pembuatan Pecah Pola Rok Di Fase E SMK Negeri 1 Wonoasri - Firda Talitha Nabila; Mita Yuniati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study develops a video tutorial learning media for the material of skirt pattern breakdown making in Phase E at SMK Negeri 1 Wonoasri, based on the Merdeka Curriculum and. The development of this media aims to: 1) describe the feasibility of the video learning media, and 2) describe students’ skills after using the video tutorial learning media for skirt pattern breakdown making. The background of this study is based on the need for more varied and interactive learning media to overcome the limitations of existing instructional media. This type of research is Research and Development (R&D) using the ADDIE model. Data were collected using two methods, namely validation sheets and assessment sheets in the psychomotor domain. The results show that: 1) the feasibility of the video tutorial learning media for skirt pattern breakdown making in Phase E at SMK Negeri 1 Wonoasri achieved an average score of 97.5%, categorized as “very feasible”, and 2) students’ skill outcomes after implementing the video media reached a classical completeness of 94% and were declared complete.